Role of RRBs in Indian Rural Economy - Singhal, R. K; Agarwal, Hari Om (Journal of Commerce and Trade, 2008)
RRBs was established in 2nd October, 1975 with the notion of augmenting the outreach of the institutional channel of credit in the remotest corner of rural India. Today they face a number of impediments in their growth. Gangible reforms are necessary to make them work in today's competitive world. RRBs have some features co-operatives and some features of commercial Banks. Like co-operatives they are rural oriented and they are familiar with rural problems. The cost of management is also low since local people are recruited at a lower salary. Side by side, like commercial banks, they operate as business organizations. They are empowered to mobilise deposits and they have access to central money market. Each RRB is a sponsored organization. It is mainly sponsored by a nationalised Commercial Bank. The sponsored commercial bank provides financial assistance to the RRB, in several ways. Besides providing share capital to RRB, the sponsored bank also provides managerial and other staff assistance. Lack of managerial efficiency is a weakness of village level cooperative societies. RRBs should have to establish their own credibility among the rural poor. This can be done only by understanding their problems and solving them properly through the timely supply of credit and other required services for their economic upliftment.